2023
DOI: 10.3847/1538-4357/acc8ca
|View full text |Cite
|
Sign up to set email alerts
|

Dark Matter in Fractional Gravity. I. Astrophysical Tests on Galactic Scales

Abstract: We explore the possibility that the dark matter (DM) component in galaxies may originate fractional gravity. In such a framework, the standard law of inertia continues to hold, but the gravitational potential associated with a given DM density distribution is determined by a modified Poisson equation including fractional derivatives (i.e., derivatives of noninteger type) that are meant to describe nonlocal effects. We analytically derive the expression of the potential that in fractional gravity corresponds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 130 publications
1
10
0
Order By: Relevance
“…In such a framework, the DM component exists, but the gravitational potential associated to its density distribution is determined by a modified Poisson equation including fractional derivatives (i.e., derivatives of noninteger type), which are meant to describe nonlocal effects; as such, this scenario is substantially different from the above theories where baryonic matter emulates DM-like effects via modifications of gravity. In [1], we showed that DM in fractional gravity worked very well for reproducing the kinematics of disk-dominated galaxies, especially dwarfs. In addition, we found preliminary evidence that the strength of fractional effects tends to weaken toward more massive systems; however, the latter finding is still subject to large uncertainties since the rotation curves of massive spirals were not probed out to radii large enough for the DM contribution to clearly emerge.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…In such a framework, the DM component exists, but the gravitational potential associated to its density distribution is determined by a modified Poisson equation including fractional derivatives (i.e., derivatives of noninteger type), which are meant to describe nonlocal effects; as such, this scenario is substantially different from the above theories where baryonic matter emulates DM-like effects via modifications of gravity. In [1], we showed that DM in fractional gravity worked very well for reproducing the kinematics of disk-dominated galaxies, especially dwarfs. In addition, we found preliminary evidence that the strength of fractional effects tends to weaken toward more massive systems; however, the latter finding is still subject to large uncertainties since the rotation curves of massive spirals were not probed out to radii large enough for the DM contribution to clearly emerge.…”
Section: Introductionmentioning
confidence: 89%
“…In fractional gravity, the potential Φ F (r) is instead derived from the modified Poisson equation [31] (−∆) s Φ F (r) = −4πG ℓ 2−2s ρ(r) (5) where (−∆) s is the fractional Laplacian operator (see [1,31] for details), s ∈ [1, 3/2] is the fractional index (this range of values for s is required to avoid divergences; see Appendix A in [1]), and ℓ is a fractional length scale that must be introduced for dimensional reasons. At variance with the standard case, the fractional Laplacian is inherently nonlocal; the index s measures the strength of this nonlocality, while the length scale ℓ can be interpreted as the typical size below which gravitational effects are somewhat reduced and above which they are instead amplified by nonlocality (around r ≈ ℓ, the dynamics is almost unaffected and indistinguishable from the standard case).…”
Section: Dm In Fractional Gravitymentioning
confidence: 99%
See 3 more Smart Citations